Analisis Memori Kolektif Sesepuh tentang Bung Karno di Blitar - Aji Subekti; Hendriyanto Hendriyanto (Media Pustakawan, 2021)
This study preserves and analyzes the typology of the collective memory of the elders, regarding Bung Karno's events and thoughts. This study uses a qualitative approach of collective memory study from Maurice Halbwachs and memory typology from Abidin Kusno. The population of this study is elders who are in Blitar with the criteria of having met and seen Bung Karno directly. The selection of informants also used a snowball sampling technique, based on key informants who had been determined by the boundaries of the elders in Blitar. The results of this study found 4 (four) treatments for this typology of collective memory, such as (1) overcoming memory, (2) unexploring memory, (3) conquering memory and, (4) marketing memory. Based on the memory typology, the researcher obtained 4 (four) concepts that can be analyzed. The first is collective memory that forms the city identity. The second is Bung Karno's thoughts on unity, and Trisakti. The third is De-Sukarnoization which means the efforts to eliminate Bung Karno's influence and thoughts as well as to obscure Bung Karno's role and contribution in history. The last is the Bung Karno Library's efforts to become a center of excellence, which is creating a database on the collective memory of elders about Bung Karno. The conclusion is that the recording and study of the collective memory of the elders completes the information needs of the community regarding oral and written sources spread throughout the Blitar community about Bung Karno.